2014
DOI: 10.1371/journal.pone.0111608
|View full text |Cite
|
Sign up to set email alerts
|

Topical Application of a Platelet Activating Factor Receptor Agonist Suppresses Phorbol Ester-Induced Acute and Chronic Inflammation and Has Cancer Chemopreventive Activity in Mouse Skin

Abstract: Platelet activating factor (PAF) has long been associated with acute edema and inflammatory responses. PAF acts by binding to a specific G-protein coupled receptor (PAF-R, Ptafr). However, the role of chronic PAF-R activation on sustained inflammatory responses has been largely ignored. We recently demonstrated that mice lacking the PAF-R (Ptafr-/- mice) exhibit increased cutaneous tumorigenesis in response to a two-stage chemical carcinogenesis protocol. Ptafr-/- mice also exhibited increased chronic inflamma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 62 publications
(97 reference statements)
0
16
0
Order By: Relevance
“…The PAR1/PAFR/MUC18 pathway regulates melanoma cell adhesion to microvascular ECs and transendothelial migration, and finally enhances metastatic seeding in the lungs [ 217 ]. Upregulation of PAFR and its agonists in this context may also impact immune functions against cancer [ 218 222 ].…”
Section: Pars Inhibitorsmentioning
confidence: 99%
“…The PAR1/PAFR/MUC18 pathway regulates melanoma cell adhesion to microvascular ECs and transendothelial migration, and finally enhances metastatic seeding in the lungs [ 217 ]. Upregulation of PAFR and its agonists in this context may also impact immune functions against cancer [ 218 222 ].…”
Section: Pars Inhibitorsmentioning
confidence: 99%
“…Studies, including ours, have shown that enzymatic (i.e., PAF) or non-enzymatically (e.g., ultraviolet B (UVB), cigarette smoke, jet fuel, and tumor promoters, such as PMA) generated PAF-R agonists mediate various pathophysiological effects, including enhanced growth of tumors in experimental models [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ]. In particular, tumor growth promoting effects can be mimicked by the administration of a non-metabolizable form of PAF (1-hexadecyl-2- N -methyl carbamoyl glycerophosphocholine (CPAF)) [ 7 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, the topical applications of CPAF suppress dimethylbenz[a]anthracene/phorbol 12-myristate 13-acetate (DMBA/PMA))-induced cutaneous non-melanoma skin cancer (NMSC) growth. The DMBA/PMA protocol is a dual chemical carcinogenesis model that induces papillomas and squamous cell carcinoma [ 7 , 19 ]. These divergent findings suggest that systemic PAF-R agonists may promote cutaneous tumors, while their topical applications may suppress them.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations